Arun Joshi’s Use of Symbolism in “The Foreigner” - Yashodhara Y. Thaker (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Arun Joshi's use of symbolism as a literary device to convey the human condition will be the topic of investigation in this paper for the study. Arun Joshi illustrates the incredible nature of human existence via symbols. An in-depth analysis of the body of work indicates that the search and the crises are the primary experiences he draws upon while writing. The author underlines Sindi Oberoi's suffering due to his adrift ness and loneliness during the novel, concentrating on Sindi's path from disengagement from the world to involvement in it. The book is about Sindi's journey from disengaging from the world to being involved. The author, Joshi, uses effective symbolism to convey the protagonist's position as someone attempting to find truth despite the chaos and meaninglessness brought on by the mind.